Conformational fluctuations of the AXH monomer of Ataxin‐1. Issue 1 (23rd November 2015) - Grasso, Gianvito; Deriu, Marco A.; Tuszynski, Jack A.; Gallo, Diego; Morbiducci, Umberto; Danani, Andrea
ABSTRACT: In this paper, we report the results of molecular dynamics simulations of AXH monomer of Ataxin‐1. The AXH domain plays a crucial role in Ataxin‐1 aggregation, which accompanies the initiation and progression of Spinocerebellar ataxia type 1. Our simulations involving both classical and replica exchange molecular dynamics, followed by principal component analysis of the trajectories obtained, reveal substantial conformational fluctuations of the protein structure, especially in the N‐terminal region. We show that these fluctuations can be generated by thermal noise since the free energy barriers between conformations are small enough for thermally stimulated transitions. In agreement with the previous experimental findings, our results can be considered as a basis for a future design of ataxin aggregation inhibitors that will require several key conformations identified in the present study as molecular targets for ligand binding. Proteins 2016; 84:52–59. © 2015 Wiley Periodicals, Inc.